2005
DOI: 10.2174/1389201054553699
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System in Space, Including Earth-Based Benefits of Space- Based Research

Abstract: Exposure to space flight conditions has been shown to result in alterations in immune responses. Changes in immune responses of humans and experimental animals have been shown to be altered during and after space flight of humans and experimental animals or cell cultures of lymphoid cells. Exposure of subjects to ground-based models of space flight conditions, such as hindlimb unloading of rodents or chronic bed rest of humans, has also resulted in changes in the immune system. The relationship of these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 59 publications
0
42
0
Order By: Relevance
“…As compared to chronic restraint stress, mice experiencing hind limb-unloading have free access to food and water and thus are not affected by starvation and dehydration whereas CRS is a more psychological stressor. Exposure to HU causes alterations in the immune system, including organ atrophy, similar to those observed after space flight (Sonnenfeld, 2005). Wei and colleagues (Wei et al, 2003) demonstrated that HU causes a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress is corticosteroid-dependent and apparently due to the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…As compared to chronic restraint stress, mice experiencing hind limb-unloading have free access to food and water and thus are not affected by starvation and dehydration whereas CRS is a more psychological stressor. Exposure to HU causes alterations in the immune system, including organ atrophy, similar to those observed after space flight (Sonnenfeld, 2005). Wei and colleagues (Wei et al, 2003) demonstrated that HU causes a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress is corticosteroid-dependent and apparently due to the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 83%
“…restraint, hindlimb unloading, stroke and microgravity) can cause the involution of the spleen and/or thymus, thus impairing the organism's ability to mount an immune response (Sonnenfeld, 2005;Dhabhar et al, 1995;Marcucci et al, 1980). The loss of spleen and thymus cellularity could be caused by one or a combination of factors, including increased cell death, reduced proliferation capacity in response to mitogenic stimulation, and redistribution of the lymphocytes in the body (Dhabhar et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with physicalrestraint stress, mice under HU have free access to food and water and thus are not transiently deprived of either. Exposure to HU causes alterations in the immune system, including immune organ atrophy, similar to those observed after space flight (23). Wei et al (24) demonstrated that HU caused a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress was corticosteroid-dependent and apparently caused by the induction of apoptosis.…”
mentioning
confidence: 83%
“…We have demonstrated that OPN is at least partially responsible for hind limbunloading (HU) stress-induced losses in peripheral lymphocytes and thymocytes (8). This type of stress leads to rapid systemic changes in stress hormone production, immune cell distribution, and cytokine/chemokine production; it also affects peripheral immune organs in the immune system (9). OPN-deficient mice showed significantly milder changes in response to this stress.…”
mentioning
confidence: 99%